Documentation of the best practices in the implementation of KALAHI-CIDSS in the municipality of Besao - Panay, Cezanne B. (2014)
This study sought to document the Best practices of Besao in the implementation of Kapitbisig Labansa Kahirapan-Comprehensive and Integrated Delivery of Social Services. Approaches and processes have become part of a development framework.The highlights in the evolution of processes and approaches are the changing dole-out paradigm to inclusive growth development paradigm and from the top to bottom planning to bottom to top planning.In general, the objective of KALAHI-CIDSS is: 1) Improve the responsiveness of local government to community needs; 2) Encourage communities to engage in development activities. 3) Deliver benefits to barangay residents through the individual sub-projects.KALAHI-CIDSS follows a community driven Strategy (People Centered Approach).CDD is operationalized through five-stage, three cycle community mobilization process called the Community empowerment Cycle or CEAC. The Three Cycle is progressive and was married with the existing cultural practices and this bore out Best Practices that can be adopted and pursued in the light of achieving Community Development. Implementation of KALAHICIDSS in Besao so far has undertaken notable implication.Findings show the following factors or practices which emerged during the implementation: 1) Inter-local Cooperation, 2) Harmonization of the KALAHI-CIDSS Processes in the Local Council Proceses 3) Adoption of the Community Plan in the Municipal Strategic Development Plan 4.Environmental Management, and 5) People’s participation and empowerment through synergized efforts between the Local Government Units and the PO’s and NGO’s.In terms of its sustainability, the interviewees observed the following challenges: interference of politics, existing laws contradicting to the procurement process of KALAHI-CIDSS, and the continuity of functionality of the organized operation and maintenance group and the organized sector.